Pengaruh Bauran Pemasaran Jasa dan Kepercayaan terhadap pembelian Online - Diah Isnaini Asiati; M. Hazazie Akbar (MBIA, 2019)
Abstract The purpose of this study ia 1) to determine the effect of products, price, process and people on trsut 2) to determine the effect of products, price, process, people, and trsut in purchasing decesion 3) to determine the effect of trust on purchasng decesion. The type of research used is associate research, to determine the relationship between the marketing mix of service and trust in online purchasing decesion. The variables used are product, prive, process, people, trust, and purchasing decesion. The sample in this study was as many as 271 respondents, with cluster sampling sampling techniques. The data used in this study are primary data, using a questionnaire method. The analysis technique used is path analysis. The results of this study indicate that simultaneously 1) there are significant influence of of products, price, process and people on trsut 2) there is a significant influence of products, prices, processes, people, and trust in purchasing decisions 3) there is a significant influence of trust on purchasing decisions. As for partially 1) only price has a significant effect on trust, while products, processes and people have insignificant influence on trust 2) only price and trust have a significant influence on purchasing decisions, while product, price, process, and people have insignificant effect on purchasing decisions 3) there is a significant influence of trust on purchasing decisions. Key words : product, price, process, people, trust, and purchasing decesion Abstrak Tujuan penelitian ini adalah 1) untuk mengetahui pengaruh produk, harga, proses, dan orang terhadap kepercayaan pembelian online 2) untuk mengetahui pengaruh produk, harga, proses, orang, dan kepercayaan terhadap keputusan pembelian online. Jenis penelitian ini adalah asosiatif, guna menentukan keterkaitan antara bauan pemasaran jasa da kepercayaan dalam keptusan pembeilan online. Variabel yang digunakan adalah produk, harga, proses, orang, kepercayaan dan keputusan pembelian. Sampel penelitian berjumlah 271 orang yang dipilih secara cluster. Data yang digunakan adalah data primer dengan metode pengumpulan data kuesioner. Teknik analisis yang digunakan adalah analisis jalur. Hasil penelitian secara simultan menunjukkan 1) Terdapat pengaruh signifikan produk, harga, proses, dan orang terhadap kepercayaan pembelian online 2) Terdapat pengaruh signifikan produk, harga, proses, orang, dan kepercayaan terhadap keputusan pembelian. Adapun secara parsial 1) Hanya harga yang berpengaruh signifikan terhadap kepercayaan, sementara produk, proses, dan orang berpengaruh tidak signifikan terhadap kepercayaan pembelian online 2) Hanya harga yang berpengaruh signifikan terhadap keputusan pembelian, sementara produk, proses, orang, dan kepercayaan berpengaruh tidak signifikan terhadap keputusan pembelian online